2017
DOI: 10.1159/000479791
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Education and Bilingualism on the Onset of Mild Cognitive Impairment

Abstract: Background: Increasing evidence suggests that life course factors such as education and bilingualism may have a protective role against dementia due to Alzheimer disease. This study aimed to compare the effects of education and bilingualism on the onset of cognitive decline at the stage of mild cognitive impairment (MCI). Methods: A total of 115 patients with MCI evaluated in a specialty memory clinic in Hyderabad, India, formed the cohort. MCI was diagnosed according to Petersen's criteria following clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 35 publications
8
29
1
Order By: Relevance
“…This discrepancy might be caused by the self-reported and less accurate questionnaire about physical activities we utilized. Hypertension, type 2 diabetes, smoking, and urban living environment were not correlated with age at AD onset, which is similar to the results of other studies [5, 7, 23, 24]. …”
Section: Discussionsupporting
confidence: 90%
“…This discrepancy might be caused by the self-reported and less accurate questionnaire about physical activities we utilized. Hypertension, type 2 diabetes, smoking, and urban living environment were not correlated with age at AD onset, which is similar to the results of other studies [5, 7, 23, 24]. …”
Section: Discussionsupporting
confidence: 90%
“…The operationalization of bilingualism differed across studies including: "had spent the majority of their lives, at least from early adulthood regularly using at least two languages" (Bialystok et al, 2007;Craik, Bialystok, & Freedman, 2010), "the ability to communicate in two or more languages in interaction with other speakers of these same languages" (Alladi et al, 2013;Alladi et al, 2017), "individuals had spent the majority of their lives, beginning at least in early adulthood, speaking two or more languages fluently-ideally daily, but at least weekly" (Bialystok et al, 2014;Chertkow et al, 2010;Ossher, Bialystok, Craik, Murphy, & Troyer, 2012), "able to communicate fluently at least in 2 languages and made regular use for both" (Estanga et al, 2017), "ability to meet the communicative demands of the self and the society in their normal functioning in 2 or more languages in their interaction with other speakers of any or all of these languages" (Ramakrishnan et al, 2017), "fluent in a second language and had used both languages consistently throughout most of his or, her life" (Schweizer, Ware, Fischer, Craik, & Bialystok, 2012), "determined on the basis of second language proficiency and frequency of use" (Woumans et al, 2015) or did not apply a specific definition Ljungberg et al, 2016;Perani et al, 2017;Wilson et al, 2015;Yeung et al, 2014;Zahodne et al, 2014). One study used more strict definitions for monolingualism and bilingualism including "speaking English for all or most of one's life and being fluent in English, but not in any other language" and "speaking both Welsh and English for all or most of one's life and being fluent in both languages, but not in any other languages", respectively (Clare et al, 2016).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Studies used different types of measurements for bilingualism (Tables 1, 2, 3, and 4). While several cross-sectional studies used validated measures including questionnaires to measure bilingualism (Bialystok et al, 2014;Clare et al, 2016;Estanga et al, 2017;Lawton et al, 2015;Ossher et al, 2012), others used non-validated methods (Alladi et al, 2013;Bialystok et al, 2007;Chertkow et al, 2010;Schweizer et al, 2012;Woumans et al, 2015), or did not report the method of collection (Craik et al, 2010;Ramakrishnan et al, 2017). Similarly, one longitudinal study assessed participants' language profiles with a non-validated measure (Wilson et al, 2015), two used a questionnaire but did not report their psychometric properties (Hack et al, 2019;Ljungberg et al, 2016), while one study validated their measure as part of the study (Zahodne et al, 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients with mild cognitive impairment (MCI), a frequent prelude of dementia, one report found that bilinguals were several years older at age of symptom onset [24]. Others found that multilinguals had a lower risk for amnestic MCI and higher temporal tissue density [25][26][27][28][29]. Another study found bilingualism associated with later age of diagnosis only among those with a low (< 11 years) educational level [30].…”
Section: Discussionmentioning
confidence: 99%